Chemical composition and thermal behaviour of tropical fat fractions from solvent-assisted process: A review - Marikkar, Mohammed Nazrim; Yanti, N.; Paciulli, Maria; Chiavaro, Emma (Chiriotti Editori, 2017)
Fractional crystallization is a process applied to plant and animal fats to obtain fat products with new functional properties and nutritional values. Fractionation is generally performed through either a dry or a solvent-assisted process. As solvents can wash off the liquid molecules able to entrap the solid component inside, the solvent-crystallization seems to be more efficient than other fractionation procedures. In recent times, fractional crystallization has been investigated for avocado (Persea Americana) butter, engkabang (Shorea macrophylla) fat, palm oil-moringa oil blend, and mee fat (Madhuca longifolia) to prepare solid (stearin) and liquid (olein) fractions. This review sums up the main and recent published studies on chemical and thermal (upon differential scanning calorimetry) properties of fat fractions obtained using solvent-assisted process. It has been argued that the ease of a fat fractionation mainly depends on the thermal characteristics of its triacylglycerol molecules. Fats with low-and high-melting thermal transitions in wide separation would yield fat components with remarkable changes in physico-chemical characteristics, fatty acid and triacylglycerol compositions as well as thermal profiles. The activities involving the use of fat components, during food formulation, may significantly benefit from a further learning of the fats behavior.